Boosting demand for orange-fleshed sweetpotato through nutrition counseling at Ghana health service facilities - International Potato Center (2017)
We introduced the pro-vitamin A-rich orange fleshed sweetpotato (OFSP) to the nutrition counselling program of the Ghana Health Service in the Northern and Upper East Regions of Ghana. In 2015 and 2016, over 8,000 pregnant or lactating women received counselling (Fig. 1), including cooking and feeding demonstrations, and were encouraged to grow or buy OFSP. In 2016, over 4,000 women received vouchers to get free samples of planting material and roots from local producers and were encouraged to buy more. At the end of the season, more than 90% indicated a willingness-to-pay for OFSP planting material and roots, and 15-16% had actually done so.